Altered instantaneous and calcium-modulated oscillatory PTH secretion patterns in patients with secondary hyperparathyroidism - Schmitt, C P; Huber, D; Mehls, O; Maiwald, J; Stein, G; Veldhuis, J D; Ritz, E; Schaefer, F (Journal of the American Society of Nephrology, 1998)
The relative contributions of increased parathyroid cell mass and altered control mechanisms of parathyroid hormone (PTH) secretion in secondary hyperparathyroidism are still controversial. In this study, endogenous pulsatile PTH secretion was analyzed by the multiparameter deconvolution technique to differentiate alterations in cell mass-dependent (PTH burst mass) and regulation-dependent (frequency, synchrony, calcium responsiveness) PTH release in uremic patients. PTH concentration versus time profiles were obtained in 13 uremic and 16 healthy adults under baseline conditions and during acute hypo- and hypercalcemia. Plasma PTH half-life was increased in patients compared with control subjects (4.7+/-1.9 versus 2.6+/-0.1 min, P < 0.005). The baseline PTH secretion rate was elevated eightfold in the patients as a result of an increased PTH mass secreted per burst (17.1+/-4.7 versus 2.0+/-0.4 pM, P = 0.0001), higher burst frequency (8.0+/-0.3 versus 6.8+/-0.3 h(-1), P < 0.01), and a higher tonic secretion rate (343+/-99 versus 30+/-4 pM/h, P = 0.0001). Acute hypocalcemia elicited an immediate, frequency- and amplitude-mediated selective increase in the pulsatile secretory component, which was fractionally weaker in patients (+595%) than control subjects (+1755%, P < 0.001). The acceleration and the amplification of PTH bursts were 35 and 60% lower in the patient group. Acute hypercalcemia suppressed total PTH secretion by 79% in control subjects but only by 63% in patients (P < 0.002). PTH burst frequency was reduced during hypercalcemia by 30% in control subjects, but remained unchanged in patients. In conclusion, uremic hyperparathyroidism is mediated by a marked increase in glandular secretion, but also by reduced PTH elimination. The increased spontaneous PTH burst frequency and the blunted responsiveness to changes in Ca2+ indicate partial uncoupling of hyperplastic parathyroid glands from the physiologic regulatory mechanisms that direct pulsatile PTH release.